2021
DOI: 10.1155/2021/6664712
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Erector Spinae Plane Block for Analgesia after Thoracotomy for Lung Transplantation in an Anticoagulated Patient

Abstract: Lung transplant recipients are at particular high risk for postoperative respiratory failure as a result of poorly controlled pain, inadequate graft expansion, decreased cough, and reliance on systemic opioid therapy. Thoracic epidural and paravertebral blocks have been employed with the goal of improving postoperative pain control, improving pulmonary mechanics, and limiting the need for narcotic administration. These approaches require a needle position in proximity to the neuraxis and may cause significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…Within this population, there were various assessments of nonopioid analgesic medications in the postoperative transplant setting. Eleven studies evaluated the impact of a single opioid‐sparing medication including pregabalin, continuous systemic lidocaine, and local anesthetics (single and continuous dosing) 18,37–46 . Furthermore, seven studies evaluated the impact of a multimodal analgesic strategies, and two assessed the impact of different education‐based interventions 19–21,47–52 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Within this population, there were various assessments of nonopioid analgesic medications in the postoperative transplant setting. Eleven studies evaluated the impact of a single opioid‐sparing medication including pregabalin, continuous systemic lidocaine, and local anesthetics (single and continuous dosing) 18,37–46 . Furthermore, seven studies evaluated the impact of a multimodal analgesic strategies, and two assessed the impact of different education‐based interventions 19–21,47–52 …”
Section: Resultsmentioning
confidence: 99%
“…Six studies were published evaluating strategies to reduce opioid use in lung transplantation 18,40,43–46 . Three of the studies were single‐center case reports/series, two were single‐center retrospective cohort studies, and one was a single‐center prospective observational trial 18,40,43,46 . A local anesthetic was used to achieve opioid‐sparing effects universally in all included evaluations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested that erector spinae plane (ESP) blocks may be an acceptable alternative to thoracic epidural analgesia in the postoperative period in thoracotomy and lung transplant patients [6][7][8]. In this case report, we describe an instance of an ESP block facilitating effective management of acute postoperative pain in lung transplant and used as a bridge to a thoracic epidural, which was eventually placed.…”
Section: Introductionmentioning
confidence: 98%